SPE Asia Pacific Oil and Gas Conference and Exhibition 2018
DOI: 10.2118/191910-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Failure of Downhole Pumps Due to Gas Interference in Coal Seam Gas Wells

Abstract: Coal seam gas (CSG) well operators typically follow an industry rule of thumb 0.5 ft/s liquid velocity to prevent the onset of gas carryover during CSG dewatering operations. However, there is very little experimental data to validate this rule of thumb with only a publication by Sutton, Christiansen, Skinner and Wilson [1] available in the open literature. A review of more general studies on two-phase gas-water flows in vertical pipes and annuli revealed that experimental conditions, especially pipe and annul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…experimentally investigated the onset of liquid flooding, wherein gas is carried downward by the liquid phase, and supported a critical superficial liquid velocity of approximately 0.152 m/s. This cut-off value was validated in Chapter 5 (Wu et al, 2018) and has been included in Figure 3-15 for comparison, showing a good overall agreement with our experimental results. Our results also indicated that the onset of liquid flooding is almost independent of gas flow rate.…”
Section: Onset Of Flooding -Counter-current Flow Limitation (Ccfl)supporting
confidence: 76%
See 2 more Smart Citations
“…experimentally investigated the onset of liquid flooding, wherein gas is carried downward by the liquid phase, and supported a critical superficial liquid velocity of approximately 0.152 m/s. This cut-off value was validated in Chapter 5 (Wu et al, 2018) and has been included in Figure 3-15 for comparison, showing a good overall agreement with our experimental results. Our results also indicated that the onset of liquid flooding is almost independent of gas flow rate.…”
Section: Onset Of Flooding -Counter-current Flow Limitation (Ccfl)supporting
confidence: 76%
“…The content of this chapter is based on: Wu, B., Firouzi, M., Rufford, T. E. and Towler, B. (2018) " et al (2006) available in the open literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation